Pelatihan Penyusunan Instrumen Tes dan Analisisnya Menggunakan Model Rasch bagi Guru di Kecamatan Subah - Muhtarom, Muhtarom; Nuvitalia, Duwi; Sutrisno, Sutrisno; Murtianto, Yanuar Hery (Perkumpulan Kualitama Edukatika Indonesia, 2026)
Efforts to improve teachers in learning evaluation require various breakthroughs. Teachers need to have the ability to prepare test instruments and carry out assessments fairly. This Community Service (PKM) activity takes the form of training in preparing test instruments for elementary school teachers in Subah District, Batang Regency. This service aims to provide teachers with understanding and experience regarding: 1) preparing questions based on high order thinking skills, 2) preparing assessment designs, 3) preparing question instruments, and 4) analyzing question items in a modern way (Item Response Theory). Service activities were carried out for three days using an andragogy approach. The training material is presented with more practice than theory, with a ratio of 25% theory and 75% practice. The results of the service show that the Wilcoxon test for pre-test and post-test scores (aspects of knowledge) can be concluded that there is a significant increase in knowledge after being strengthened in the concept of assessment, instrument preparation and Rasch analysis. Meanwhile, the skill aspect experienced a significant increase after the Rasch data processing practice activities were carried out. The N-Gain results of the knowledge and skills aspects obtained high improvement results. This shows that there has been an increase in knowledge and skills after mentoring and training in rasch analysis and can help teachers in Subah District, Batang Regency in developing learning evaluation competencies.